The Analysis of Misconceptions in Simple Airplane Material for 8th Grade Students in SMP Muhammadiyah 3 Gorontalo - Fahrunissa, Putri; Buhungo, Trisnawaty Junus; Pikoli, Masrid (SEJ (Science Education Journal), 2023)
This study aims to (1) determine students' conception maps in simple machine material (2) analyze students' misconceptions in simple machine material. This research is a descriptive research. The research subjects were class VIII of SMP Muhamadiyah 3 Gorontalo City with a sample size of 25 students. The/research data were obtained from students' answers through a three-level multiple-choice diagnostic test (Three Tier Multiple Choice) and processed based on the pattern of student answers grouped into categories of understanding the concept, misconception 1, misconception 2, misconception 3 and not understanding the concept. The results showed that category 1 misconception had a percentage of 23%, misconception 2 had a percentage of 17%, and misconception 3 had a percentage of 25%.